Deteksi Gen Jamur Candida spp. pada Swab Tenggorok Penderita Tuberculosis dengan Metode Polymerase Chain Reaction - Yulianingsih, Aan; Basri, Acce; Jakaria, Febrianti (Poltekkes Kemenkes Kendari, 2022)
Pulmonary tuberculosis is the leading cause of death associated with the Mycobacterium tuberculosis complex globally. The incidence of tuberculosis is calculated as dividing the number of new cases of the disease in a year in one hundred thousand population. Many risk factors associated with TB are coinfection with the fungus Candida spp. Coexistence between fungal pathogens and pulmonary TB is a common clinical condition in immunosuppressed patients. Thus, there is a need for screening in patients with tuberculosis co-infected with Candida spp, especially in cases of patients with inadequate response to OAT therapy. The purpose of this study was to determine the candida spp gene in throat swabs of TB patients at the Kalumata Health Center. The method used is descriptive analytic with a cross sectional design. The genes used were C. albicans (665 bp), C. Parasilopsis I (837 bp), C. Parasilopsis II (310 bp), C. guilliermondii (205 bp) and C. lusitaniae (799 bp). The results showed that from 30 samples found 7 sampels (23,3%) Candida albicans species, Candida parasilopsis II as many as 8 samples (26.7%) and 15 samples were negative (50%). The conclusion of this study is that from 30 samples, 15 samples were detected that had the Candida spp gene.